2018
DOI: 10.1002/eat.22929
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of reviews of neurocognitive functioning in eating disorders: The state‐of‐the‐literature and future directions

Abstract: While these reviews have generally suggested varying patterns of neurocognitive deficits across EDs, there remain critical limitations regarding the methodological quality of these studies (e.g., the lack of prospective designs, consideration of confounding influences, or examination of interrelationships between neurocognitive domains and relationships between neurocognition and other relevant behavioral constructs). Specifically, we outline 10 key areas that are imperative to address in future research in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 124 publications
3
111
3
Order By: Relevance
“…Moreover, several studies have demonstrated an increased risk of co-occurrence of the two disorders [9,11], with rates of AN varying between 11-13% in clinical OCD populations and rates of OCD between 9.5 and 62% in patients with a primary diagnosis of AN. Patients with OCD and AN also share specific inefficiencies in executive functioning, most commonly in set-shifting/cognitive flexibility, visuospatial abilities, processing speed, motor inhibition, and working memory [12][13][14][15][16][17][18][19]. These inefficiencies have been associated with frontostriatal abnormalities in functional neuroimaging studies [20][21][22]; they are assumed to be central to the development and maintenance of obsessive thoughts and compulsive behaviors in both OCD and AN [23,24] and thought to interfere with a patient's ability to acquire and use concepts trained in psychotherapy, most particularly cognitive therapies [25], where the traits negatively affect treatment motivation and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated an increased risk of co-occurrence of the two disorders [9,11], with rates of AN varying between 11-13% in clinical OCD populations and rates of OCD between 9.5 and 62% in patients with a primary diagnosis of AN. Patients with OCD and AN also share specific inefficiencies in executive functioning, most commonly in set-shifting/cognitive flexibility, visuospatial abilities, processing speed, motor inhibition, and working memory [12][13][14][15][16][17][18][19]. These inefficiencies have been associated with frontostriatal abnormalities in functional neuroimaging studies [20][21][22]; they are assumed to be central to the development and maintenance of obsessive thoughts and compulsive behaviors in both OCD and AN [23,24] and thought to interfere with a patient's ability to acquire and use concepts trained in psychotherapy, most particularly cognitive therapies [25], where the traits negatively affect treatment motivation and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been suggested that cognitive schemas of individuals with EDs facilitate processing of appearance‐related information (Vitousek & Hollon, ), that cognitive rumination exacerbates and maintains negative affect in EDs (Smith, Mason, & Lavender, ), and that attentional biases may maintain ED symptoms by directing cognitive resources toward disorder‐salient stimuli, thereby interfering with tasks and distorting interpretations about the environment (Aspen, Darcy, & Lock, ; Stojek et al, ). In recent years, several cognitive processes that are thought to be relevant to EDs have been investigated by measuring individuals' performances on behavioral tasks, though this work has largely been limited to laboratory settings (Smith, Mason, Johnson, Lavender, & Wonderlich, ).…”
Section: Resultsmentioning
confidence: 99%
“…Neurocognitive functioning may be altered among individuals with eating disorders (EDs), with differences noted across several neurocognitive domains, including attention, working memory, and inhibitory control (Smith, Mason, Johnson, Lavender, & Wonderlich, ). A recent systematic review noted that patterns of neurocognitive functioning in EDs vary across ED subtypes and highlighted the paucity of prospective research designs that can effectively answer whether neurocognitive differences exist prior to the onset of EDs or are a consequence of these disorders (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurocognitive functioning may be altered among individuals with eating disorders (EDs), with differences noted across several neurocognitive domains, including attention, working memory, and inhibitory control (Smith, Mason, Johnson, Lavender, & Wonderlich, ). A recent systematic review noted that patterns of neurocognitive functioning in EDs vary across ED subtypes and highlighted the paucity of prospective research designs that can effectively answer whether neurocognitive differences exist prior to the onset of EDs or are a consequence of these disorders (Smith et al, ). Temporality has been explored by comparing individuals in recovery from EDs with healthy controls with mixed findings (Lozano‐Serra, Andrés‐Perpiña, & Lázaro‐García, ; Tchanturia et al, ), though it is also possible that alterations in neuropsychological functioning among recovered individuals represent a “scar” of the illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation